Variance and Control in Experimental ResearchSiti Aulia Putri - Siti Aulia Putri (PT. Anagata Sembagi Education, 2024)
Variance in experimental research refers to variations or differences in the observed data. Variance can arise from various sources, such as individual differences, environmental conditions, or other undesirable factors. The importance of understanding variance is that it can affect the validity of experimental results. Variable control in experimental research is an attempt to minimize irrelevant variance and ensure that observed differences are directly attributable to the independent variables manipulated in the study. This is done by designing the experiment in such a way that confounding factors are controlled or limited as much as possible. The experimental research method aims to find the effect of certain treatments on others under controlled conditionsVariance in experimental research can be further analyzed into several types of variance, while researcher control in experimental research concerns independent variables (VB) and secondary variables (VS). Various control techniques are used to ensure the success and validity of experimental research, such as randomization, elimination, constancy, matching, blocking, making the secondary variable the second independent variable, statistical control, and counterbalancing. Variance is an important tool in statistical analysis used to analyze factors that affect the distribution or spread of data. Control is an important feature in scientific research, especially in experimental research. Variance and control are important aspects of experimental research to ensure the validity and reliability of findings.